Cytotoxicity of HA-TCP Scaffold on Human Umbilical Cord Mesenchymal Stem Cells using MTT Assay - Ariestania, Vivin; Hendrijantini, Nike; Prahasanti, Chiquita; Prasetyo, Eric; Kuntjoro, Mefina; Parwati Sari, Rima; Dwi maharani, Aulia (International Journal of Integrated Engineering, 2022)
Background: Hidroxyapatite-tricalciumphospate (HA-TCP) scaffold is a three-dimentional structure used to support bone regeneration. Ideally, the scaffold should be biocompatible, biodegradable and non-toxic. The tissue engineering technique uses a combined stem cell and scaffold to repair a bone defect. To prove the nontoxic properties of the scaffold, a cytotoxicity test is needed for the human umbilical cord mesenchymal stem cell (HUCMSCs). Methods: 27 samples were divided into 8 groups with variant of  scaffold HA-TCP doses ranging from 5-1000 micrograms. Each treatment group of scaffolds was covered in HUCMSCs. The samples were added by methyl-thiazol-tetrazolium (MTT) colorimetric assay and counted used an optical density (OD) formula and then  observed by microplate reader. The viability of the cells was observed by an inverted TMS microscope with 100x magnification. Result: MTT assayâ€™s test shows that the HUCMSCs cell viability shed each variant of HA-TCP scaffold dose, did not show any toxic effect. The higher the OD value the higher the viability. Conclusion: There is no significant difference between the variable scaffold doses to the percentage viability of umbilical cord cells.